Working hard, working poor a global journey - Fields, Gary S. (New York ; Oxford : Oxford University Press, 2011)
More than three billion people in the world live on less than two-and-a-half U.S. dollars per person per day. In this book Gary Fields explains how the poor work, how they have improved their self-employment earning opportunities, how poor-country governments can stimulate more inclusive economic growth, and how they can be aided.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Working poor -- Developing countries; Labor market -- Developing countries